Research progress of continuous care of patients after percutaneous coronary intervention (经皮冠状动脉介入治疗术后患者延续性护理的研究进展) - JIA Hongwei (贾红薇); LIU Ning (刘宁); QI Yanchun (齐艳春); (韩平平); LI Rongyan (李荣艳); WANG Lijun (王丽君); SHAN Xiaoyan (单晓燕); YANG Lin (杨林) (中西医结合护理)
Continuous nursing has a high research value in postoperative rehabilitation nursing, and has a certain effect on improving the postoperative prognosis of patients with coronary heart disease. Percutaneous coronary intervention (PCI) is a non-surgical, invasive procedure with advantages of minimal incision and fast recovery in the treatment of coronary heart disease. The secondary prevention after PCI is of great significance for prevention of disease recurrence and adverse prognosis. This study reviewed the research status of continuous nursing of patients after PCI, with a view to improving the quality of life and self-management ability of patients (延续性护理在术后患者康复护理中展现了良好的应用价值。经皮冠状动脉介入治疗术(PCI)具有创伤小、恢复快等优势, 是临床治疗冠心病(CHD)患者的常用方案。PCI术后二级预防对避免CHD复发和不良预后有着重要意义。本研究就PCI术后患者的延续性护理应用现状进行综述, 旨在为进一步提高PCI术后患者疾病自我管理能力、改善生活质量提供参考。)